The Shaman's Share, or Inuit Sexual Communism in the Canadian Central Arctic - d'Anglure, Bernard Saladin; Philibert, Jane (Anthropologica, 2022)
Contemporary anthropology has had difficulties in classifying or interpreting Mauss and Beuchat's Essay on Seasonal Variations in Eskimo Societies, and has mostly remembered the seasonal dualism of the social morphology. It is tempting to discover in this Essay the underlying influence of Mauss's own political commitment and his leanings toward a humanistic socialism. Fascinated as he was by the intensity of the winter social life of the Inuit, in all economic, jural, religious and sexual domains, Mauss does not hesitate to call it sexual and economic communism, as opposed to the summer individualism of conjugal families. In the light of recent ethnographic data, concerning the central Arctic Inuit exchange of spouses, in both the restricted form between couples and the generalized one during the winter solstice festival (which Mauss viewed as the crux of social communion), the author proposes to transcend the somewhat reductionist dualism of the Essay, employing a ternary and hierarchical approach, inspired in part by Louis Dumont. The figure of the shaman, a "third gender" and mediator, then appears as the main operator of spouse-exchanges, in a context of sexual markings imposed upon women and communal violence inflicted on young people, particularly young couples. These have to undergo the sharing of their production, of their offspring and of their sexuality, for the benefit of older people, mature men and especially shamans. Individualism and communism are then in a conjunctive relationship in the dualistic play of seasons